Language Philosophy and Changes in Meaning in Digital Culture - Rizka Auliya Jufri; Hasnah Faizah; Lisdawati Lisdawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the semantic shift in language within digital culture through the perspectives of linguistics and the philosophy of language. The focus of the study is directed toward the phenomenon of memes, emojis, abbreviations, and popular expressions that have rapidly developed on social media platforms and often deviate from their standard meanings. The research employs a descriptive qualitative method using content analysis combined with a philosophical literature review. Data were obtained from various digital platforms such as Instagram, TikTok, and Twitter/X, as well as relevant academic sources. The results indicate that semantic shifts in digital language occur through patterns of meaning expansion, metaphorization, polysemy, and linguistic innovation. From the standpoint of the philosophy of language, these findings align with Wittgenstein's meaning is use theory and Austin's speech act theory, both of which emphasize that meaning is determined by the practical use of language and speech acts within social contexts. Thus, the changes in meaning in digital culture are not merely linguistic but also reflect the social, cultural, and technological dynamics that shape modern communication patterns.